Efficacy of chlorophyll a fluorescence kinetics and JIP test for early detection of leaf-gall disease in Cordia dichotoma - Bhatt, Upma; Anjana, Vipul; Soni, Vineet (Journal of Plant Stress Physiology, 2024)
Gall-induced oxidative stress impairs photosynthesis and ultimately negatively affects a plant’s productivity and yield. Cordia dichotoma is an economically important plant that suffers from galls produced by the insect Aceria gallae. So we investigated how plants deal with such biotic stress by studying chlorophyll fluorescence OJIP transient analysis. The results indicate the intensive variations in minimum-maximum fluorescence, electron transport, light-harvesting efficiency and density of active reaction centers. When reaction centers become inactive in severely infected leaves a significant rise in ABS/RC and TR/RC indicates the expanded antenna size of Photosystem-II which shows the plant’s efforts to enhance photon absorption. But the electron transport was blocked due to OECs deactivation, remarkably altered ET/RC and phenomenological fluxes (ABS/CS, TR/CS and ET/CS). The J-curve distortion confirms blockage of electron transport towards PS-I since PQ is fully reduced and unable to grape electrons from QB. Leaf galls carry out noteworthy alterations in Kp, Kn, and primary and secondary photochemistry. But more severe infection causes complete obstruction for electron transport which finally diminishes performance indices (PIabs and PIcs) quantum yield of photosynthesis (φPo), and electron transport (φEo) which increases dissipation and eventually causes the death of the most severely infested leaf. Present studies reveal that measurement of FV/F0, PIabs, and PIcs may be used as a physiological marker for the early diagnosis of gall stress in C. dichotoma. Our results also suggest that repetitive detection of photosynthetic performance through chlorophyll a fluorescence analysis and a JIP-test can be used as potent tools to prevent plants from appearing the visible symptoms of any pathogenic infection.